The effectiveness of citizen journalism in Kazakhstan - Toktarbai, Б.; Zhaksylyk, А. (Bulletin of L.N. Gumilyov Eurasian National University. JOURNALISM Series, 2022)
Now in Kazakhstan, the active involvement of citizens in any business is more advanced than in previous years. The efforts of the authorities to listen to the voice of civil society also lead to a positive trend. The head of state, taking the initiative, constantly encourages the support of civil society, fulfilling their wishes and jointly forming the future strategy of the state. The appearance of the «National Council», which brings together public figures, civil society activists and representatives of the government on one table, is a clear proof of this. At the same time, the creation of the «Great kurultai», dedicated to the upcoming joint discussion of important issues of the state with public activists, can be understood as a good step towards the development of civil society in Kazakhstan. The only means of bringing the voice of civil society to power is the social network, the power of civil journalism. In this article, we will analyze the energy and activity of civil journalism in Kazakhstan and the level of consumption of social networks by the country’s population.